2018
DOI: 10.1002/mp.13091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interfractional motion on hypofractionated pencil beam scanning proton therapy and VMAT delivery for prostate cancer

Abstract: The robustness of PBS and VMAT were comparable for all patients for the studied fractionations. The delivered target dose generally remained within clinical tolerance and the deviations were relatively minor for both fractionation schemes. The delivered OAR dose stayed in compliance with the RTOG hypofractionation constraints for all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…One study evaluated patients receiving adjuvant RT of the prostate bed after prostatectomy 32 . While a 3‐4 mm posterior margin was considered as too small in some studies, 25,32,33,35 it was found adequate in others 26,36–38 . However, the direct quantitative comparison of the studies is hindered by the diverse dosimetric criteria which were used to judge target coverage as adequate and the different navigation techniques applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study evaluated patients receiving adjuvant RT of the prostate bed after prostatectomy 32 . While a 3‐4 mm posterior margin was considered as too small in some studies, 25,32,33,35 it was found adequate in others 26,36–38 . However, the direct quantitative comparison of the studies is hindered by the diverse dosimetric criteria which were used to judge target coverage as adequate and the different navigation techniques applied.…”
Section: Discussionmentioning
confidence: 99%
“…On A number of previous studies analyzed dosimetric consequences of interfractional CTV displacements and deformations by means of dose accumulation to evaluate appropriate PTV margins, based on weekly MV-CBCTs, 32 daily kV-CBCTs, [33][34][35] helical MVCTs 36 or repeat planning CTs. 25,26,37,38 Only in two studies, an endorectal balloon was used. 36,37 The majority of the studies analyzed patients treated with definitive RT.…”
Section: Sfmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated inter-fractional prostate variability by means of repeated CT, kV or online CBCT (for a review on this topic, see [8] ). Mean prostate displacements of up to 9 mm between fractions have been reported, with the largest deviation found in the anterior-posterior (AP) direction [8] , [9] . Seminal vesicles, which are included in the target volume for intermediate and high risk disease patients, are subjected to even larger inter-fractional shifts than the prostate [10] .…”
Section: Introductionmentioning
confidence: 99%